Human CD8+CD28− T suppressor cells expanded by common gamma chain (γc) cytokines retain steady allospecific suppressive capacity in vivo - Guihuan Liu (BMC Immunology, 2020)
Abstract Background CD8+CD28− T suppressor (Ts) cells play critical role in transplant tolerance. Our previous study has generated CD8+CD28− Ts cells in vitro which exert robust allospecific suppressive capacity in vitro. Results CD8+CD28− Ts cells were expanded by stimulating human CD8+ T cells with allogeneic antigen presenting cells in the presence of the common gamma chain cytokines IL-2, IL-7 and IL-15 in vitro, and were further verified in vitro through day 7 to 11 for their persistency of the allospecific suppressive capacity. When CD8+CD28− Ts cells were adoptively transferred into NOG mice, their capacity to inhibit CD4+ T cell proliferation in allospecific manner remained potent on 11 days after their injection. The mechanisms for expansion of CD8+CD28− Ts cells by the common gamma chain cytokines were investigated. These included promoting CD8+CD28− T cells proliferation, converting CD8+CD28+ T cells to CD8+CD28− T cells and decreasing CD8+CD28− T cell death. Furthermore, the expanded CD8+CD28− Ts cells showed upregulation of the co-inhibitory molecule Tim-3 and down-regulation of the cytotoxic molecule granzyme B. Conclusions In summary, these results demonstrated that the in vitro-expanded human CD8+CD28− T cells retained potent allospecific suppressive capacity in vivo and depicted multiple mechanisms for the expansion of Ts cells, which might promote further bench to clinic research.